STRATEGI PEMERINTAH DALAM PEMBERDAYAAN PEREMPUAN DI DESA CARAWALI - S, Sartika (Universitas Gajah Putih, 2025)
. Women's empowerment is an important issue in socio-economic development, especially in rural areas that still face gender disparities. This study aims to analyze the government's strategy in empowering women in Carawali Village and identify the obstacles faced in its implementation. Using a qualitative approach with thematic analysis techniques assisted by NVivo software, data were collected through observation, in-depth interviews, and documentation. The results of the study show that the strategies used by the village government include persuasive and cultural approaches through informal forums such as pengajian, arisan, dasawisma, skills training, cross-institutional cooperation, and the formation of study groups. This approach has proven effective in building trust and increasing women's participation, but still faces various obstacles such as feelings of inferiority, cultural pressure, limited funds, and a lack of professional trainers. NVivo analysis strengthens the finding that the persuasive approach is the most dominant strategy, while fear and limited resources are the main challenges. The success of women's empowerment in Carawali Village is highly dependent on the strategies used and the support of the surrounding social environment.